Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcimb.2021.696379
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium tuberculosis Complex Bacilli and Nucleic Acids From Tongue Swabs in Young, Hospitalized Children

Abstract: Diagnosis of tuberculosis in pediatric patients remains challenging due to inherent difficulties associated with obtaining respiratory samples for molecular and culture-based testing. To address this, recent studies have highlighted the utility of tongue swabs to detect Mycobacterium tuberculosis genomic DNA in the oral epithelia of tuberculosis infected adults. It is unknown whether tongue swabs have similar utility for diagnosis of childhood tuberculosis and if the presence of DNA in these swabs was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Using an alternative processing method, where a single swab was boiled, incubated, and mixed without using sample reagent, sensitivity was very similar at 77% (60–90) and specificity was 100% (16–100). 21 With the increased biomass collected by double swabs, the processing method using Cepheid sample reagent showed similar sensitivity to the boil method (73% using the Cepheid sample reagent vs 77% using the boil method). The use of sample reagent and similar processing methods to sputum potentially allows laboratories already performing sputum testing with Xpert MTB/RIF Ultra to use oral swabs as a sample type with minimal change in processing methods.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Using an alternative processing method, where a single swab was boiled, incubated, and mixed without using sample reagent, sensitivity was very similar at 77% (60–90) and specificity was 100% (16–100). 21 With the increased biomass collected by double swabs, the processing method using Cepheid sample reagent showed similar sensitivity to the boil method (73% using the Cepheid sample reagent vs 77% using the boil method). The use of sample reagent and similar processing methods to sputum potentially allows laboratories already performing sputum testing with Xpert MTB/RIF Ultra to use oral swabs as a sample type with minimal change in processing methods.…”
Section: Discussionmentioning
confidence: 91%
“… 20 One study was considered high concern for applicability for patient selection, as it was carried out in a tertiary care referral hospital; however the study was carried out in a population of children with a relatively high prevalence of HIV (17·1%), both of which are target population characteristics for non-sputum-based diagnostic samples. 21 All studies were assessed as unclear concern for applicability of the index test as there is no standard methodology defined for using oral swabs for tuberculosis detection. All studies were considered low risk of bias in the reference test domain, and 18 were assessed as low risk of bias in the flow and timing domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Cox et al found that the yield of microbiologic confirmation using oral swab specimens in children with pulmonary TB was suboptimal ( 18 ). Flores et al demonstrated that tongue swabs can be employed for diagnosing TB in children who are clinically diagnosed with TB but are unable to produce sputum samples ( 33 ). Nevertheless, interpretation of these results requires caution as the number of studies on diagnosing OSA in children with pulmonary TB and HIV-positive individuals with pulmonary TB is limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of cheek swabs have been assessed in adults living with HIV (LaCourse et al, 2022). While tongue swabs were evaluated in young children, a population were traditional sputum samples are not easily obtained (Ealand et al, 2021).…”
Section: Case Findingmentioning
confidence: 99%